Symposium 6: Practice Firms and Networked Learning: Unaccomplished Potentialities - Santos, Jorge Alberto dos (Proceedings of the International Conference on Networked Learning, 2006)
The aim of this paper is to present and discuss some aspects of networked learning in “Practice Firms”. Practice Firms (PF) are simulated learning environments where participants operate fictitious companies creating a virtual market of nearly 4,000 similar companies in 39 different countries. This results in a network of approximately 50,000 students around the world. The interviews of this study were carried out in Austria and Brazil using a phenomenographic approach (Marton 1986); (Marton and Booth 1997) and employed Bowden's (2000) phenomenographic perspective called “developmental phenomenography”. The main conclusion is that the PF network has an enormous potential for improving management learning but needs to overcome structural and dynamic drawbacks.